The Role Of Sociolinguistic And Sociopragmatic In The Development Of Language Learning In Elementary School - Zulkhaeriyah, Zulkhaeriyah; Kamsinah Kamsinah; Nurasia Natsir; Ainun Fatimah (Cita konsultindo, 2022)
The purpose of this study is to discover the role of Sociolinguistic and Sociopragmatic for primary school students in the developmental process of language learning by children. School-aged children find themselves in a developmental phase where they organize and integrate a variety of developmental skills to adapt to increasingly complex tasks, including language development. Language development is essentially a person's ability to communicate with their surroundings. Communication is used to build relationships with others in order for us to feel part of the environment. Language skills develop throughout the school year. Students are increasingly able to better understand and interpret spoken, written and body language communications, enabling them to understand the context and understand the people around them. Language development is related to cognitive development, meaning that intelligence factors and understanding of the environment around children greatly influence the development of their language skills. As children grow and develop, their language skills begin to develop from very basic to complex levels. Language development is influenced by the environment because language is essentially the result of learning from its environment. Children learn languages ​​and other things by imitating and repeating words used by adults. their language skills start to develop from a very basic level to a complex level. Language development is influenced by the environment because language is essentially the result of learning from its environment. Children learn languages ​​and other things by imitating and repeating words used by adults. their language skills start to develop from a very basic level to a complex level. Language development is influenced by the environment because language is essentially the result of learning from its environment. Children learn languages ​​and other things by imitating and repeating words used by adults.